STUDI FENOMENOLOGI: PENGALAMAN ORGANISASI SATGAS PPKS UPN "VETERAN" JAKARTA DALAM PENCEGAHAN KEKERASAN SEKSUAL - Alda Nadia Rahmayani (2023)
Prevention of sexual violence is needed as an effort to reduce cases of sexual violence in higher education, because sexual violence is a problem that has long been a public issue, cases of sexual violence in universities increase every year. Therefore, every university in Indonesia is required to form a task force organization whose role is to prevent sexual violence on campus. This study aims to determine the organizational experience of the UPNVJ PPKS Task Force in preventing sexual violence. This research uses a qualitative research method with a phenomenological approach conducted to the UPNVJ Task Force for the Prevention and Handling of Sexual Violence (Satgas PPKS) using 5 informants and this research uses phenomenological theory. The results of this study found that the organizational experience of the UPNVJ PPKS Task Force in preventing sexual violence uses direct socialization (in the form of talk shows and meetings with campus organizations) and media socialization (in the form of Instagram social media, audio visuals, and posters) aimed at the academic community to provide educational messages related to sexual violence that help reduce and prevent sexual violence in the university environment.